Core processing, analysis and transportation procedures at Site J, Greenland (JAGE-89) - Hitoshi Shoji; Hideki Narita; Kokichi Kamiyama (National Institute of Polar Research, 1991)
The field activities of the Japanese Arctic Glaciological Expedition (JAGE-89; PI, O. WATANABE) were conducted at Site J, West Greenland (66°51.9′N, 46°15.9′W) during the period of May to June in 1989. The main objective of the JAGE-89 field operation by eight members (field leader, Y. FUJII) was to drill, process and analyze shallow ice cores in the field and transport some of them into Japan for further analyses. Such investigations will make clear the environmental record preserved in the Greenland ice sheet. Two ice cores were obtained. 101m and 206m long each, by using two sets of electro-mechanical drills. Physical property studies of the fresh ice cores were conducted, immediately after each core portion was recovered in the field. These studies include measurements on ECM, stratigraphy, bulk density, and others. Electrical conductivity and pH measurements were also carried out on melted samples. The rates of core drilling and processing/analyzing were almost equal to each other; ca. 10m/day. After the field operations, the total weight of 720kg of core samples were transported to Japan for further laboratory studies.